2012
DOI: 10.1309/ajcphc85dgaxzdbe
|View full text |Cite
|
Sign up to set email alerts
|

p53 Nuclear Expression Correlates With Hemizygous TP53 Deletion and Predicts an Adverse Outcome for Patients With Relapsed/Refractory Multiple Myeloma Treated With Lenalidomide

Abstract: del(17p13)(TP53) seems to be an independent poor prognostic factor in patients with relapsed/refractory multiple myeloma (MM) receiving lenalidomide. However, whether aberrant p53 nuclear expression detected by immunohistochemical analysis can be used as a surrogate marker for del(17p13)(TP53) in prognostic evaluation of lenalidomide-treated relapsed/refractory MM remains unclear. The p53 expression in myeloma cells from 88 patients was evaluated by immunohistochemical analysis, and 17p13(TP53) gene status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
3
22
0
1
Order By: Relevance
“…18,[23][24][25][29][30][31][32][33][34] TP53 mutations occur primarily in high-risk/therapy-related MDS, MDS-derived leukemia, and in the context of complex chromosomal abnormalities including del(17p). 11,12,14,15,[18][19][20]35,36 Studies also reported on the poor prognostic impact of TP53 mutations and the association between TP53 mutations and poor therapy response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[23][24][25][29][30][31][32][33][34] TP53 mutations occur primarily in high-risk/therapy-related MDS, MDS-derived leukemia, and in the context of complex chromosomal abnormalities including del(17p). 11,12,14,15,[18][19][20]35,36 Studies also reported on the poor prognostic impact of TP53 mutations and the association between TP53 mutations and poor therapy response.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Recently, it was demonstrated that p53 nuclear expression correlated with hemizygous TP53 mutation and outcomes in relapsed myeloma patients treated with lenalidomide. 25 AML following MDS has a dismal prognosis, which makes prediction essential, especially in patients who potentially could be cured by stem cell transplantation. In order to develop a clinically useful prognostic tool, we measured p53 protein expression by IHC in a cohort of 85 patients with lower-risk del(5q) MDS from the MDS-004 clinical trial, and compared outcomes and responses to lenalidomide treatment in patients with respect to strong nuclear p53 expression.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Thus, the immunohistochemical detection of p53 protein suggests an underlying mutation in the gene (7). It has been previously demonstrated that aberrant nuclear expression of p53 protein is associated with hemizygous p53 deletion in multiple myeloma (8,9) and chronic lymphocytic leukemia (10). In MDS, immunohistochemical staining for TP53 protein in bone marrow trephine biopsies has revealed a strong correlation with TP53 mutation status (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to point mutations in the p53 gene that lead to inactivating amino-acid substitutions, complete loss of one or both p53 alleles through chromosomal deletions is also observed in cancer. In MM, deletion of the chromosomal arm where p53 is located (17p) is detected in approximately 10% of newly diagnosed patients and is an indicator of very poor prognosis (Boyd et al, 2011;Chen, Tai, et al, 2012;Chen, Qi, Saha, & Chang, 2012;Fonseca et al, 2003;Lodé et al, 2010). Interestingly, it was shown that in the cohort of patients with 17p deletions, the remaining allele of p53 was prone to mutation with 37% of patients presenting with mutations (Lodé et al, 2010).…”
Section: Mdm2 Inhibitorsmentioning
confidence: 99%
“…The inhibition of STAT3 by sorafenib is independent of Raf kinase inhibition, which was determined by Chen et al (2011) who synthesized sorafenib derivatives that lacked binding affinity for the Raf kinase domain but retained the capacity to inhibit STAT3. Inhibition of STAT3 by sorafenib and derivatives was proposed to occur via activation of the Src homology protein tyrosine phosphatase SHP-1 (Chen, Tai, et al, 2012;Chen, Qi, et al, 2012), which inhibits STAT3 phosphorylation. Numerous preclinical studies have demonstrated a promising anti-MM activity of sorafenib, both as a single agent and in combination with Btz (Kharaziha et al, 2012;Ramakrishnan et al, 2010;Udi et al, 2013).…”
Section: Il-6/stat3 Signaling Axismentioning
confidence: 99%